Pengaruh Bermain Terapeutik Mewarnai Terhadap Motorik Halus Anak Kebutuhan Khusus Autis Usia Sekolah Di Sekolah Luar Biasa Pelita Hati Jakarta - Tatiana Siregar; Novita Ayuni Kardiyanti (Jurnal Persada Husada Indonesia, 2019)
Children with Special Needs with autism have a delay in fine motor development. This study aims to determine the effect of coloring therapeutic play on fine motor skills of school-aged children with autism in the Pelita Hati School Jakarta. The study was conducted from April to July 2017. The design of this research design was quasi-experimental with the Pre and Post Test Control Group Design approach. The total sample of 12 children with a total sampling technique. Based on the Paired Sample T-test, there was an influence of playing therapeutic coloring on fine motor in the control and intervention groups with p Value 0.005 and 0.002 (p <0.05; 95% CI). There were significant differences in fine motor skills in the control and intervention groups during the pre-test and post-test with p values ​​of 0.0465 and 0.0005 (p <0.05; 95% CI). It is expected that school institution can implement continuous teraupeutic play, in order to improve the fine motor skills of autistic special need children through innovative terupeutic playing programs.